The Genesis of Argumentation: A Study of 3-5-year-old children in Different Contexts of Play - Migdalek, Maia Julieta; Rosemberg, Celia Renata; Santibáñez Yáñez, Cristian (Íkala, Revista de Lenguaje y Cultura, 2015)
<!– [if gte mso 9]> <![endif]–> This work aims to analyze the development of the argumentative strategies in three, four and five years old children. In a previous study we developed a system of categories that conceptualize the argumentative strategies used by children of this age. In this study we analyze the argumentative strategies as well as the linguistic resources used by the children in disputes that occurred during play situations at kindergarten. The analysis considers children ́s performance taking into account the age group and the type of play (dramatic play, board game and block play). The corpus consists of 124 disputes among peers. Results show that at four and five years of age there are significant differences between the quantity of argumentative strategies employed by the children and the quantity of occasions in which they just oppose a point of view. Regarding the type of play, we found significant differences between the quantity of argumentative strategies used by the children and the occasions in which they just oppose a point of view during the three types of play analyzed: dramatic play, block play and board game. Results are discussed considering previous studies that showed that age four could be a turning point where early skills of argument arise. Results also showed that not only dramatic play situations but also block play and board game situations create opportunities for children to use argumentative strategies. <!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–>